2018
DOI: 10.1111/inm.12472
|View full text |Cite
|
Sign up to set email alerts
|

Generalist health professional's interactions with consumers who have a mental illness in nonmental health settings: A systematic review of the qualitative research

Abstract: Generalist health professionals (GHPs) or those healthcare professionals working in nonmental health facilities are increasingly being required to provide care to consumers with a mental illness. The review aimed to synthesize the qualitative research evidence on the meanings and interpretations made by GHPs (nonmental health professional) who interact with consumers with mental illness in nonmental health settings. A systematic review of the qualitative literature was undertaken for the years 1994-2016. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In another finding consistent with our results, Brunero et al (2018) found need for knowledge was a theme in their literature review of general nurses' interactions with mental health consumers, although in contrast to Brunero et al's findings of lack of confidence, nurses in the current study reported high levels of confidence in working with mental health consumers. There was a strong endorsement of the need for further training in this area.…”
Section: Ta B L E 4 (Continued)supporting
confidence: 88%
“…In another finding consistent with our results, Brunero et al (2018) found need for knowledge was a theme in their literature review of general nurses' interactions with mental health consumers, although in contrast to Brunero et al's findings of lack of confidence, nurses in the current study reported high levels of confidence in working with mental health consumers. There was a strong endorsement of the need for further training in this area.…”
Section: Ta B L E 4 (Continued)supporting
confidence: 88%
“…General Practitioners are often required to provide care outside of their clinical speciality. In addition to educational programs, organisational and system-level changes are needed to ensure the quality of care provided to those experiencing mental health concerns is consonant with their needs [44]. Alternative understandings of suicidal distress, coupled with stigma or previous negative experiences of treatment and care, may also reasonably explain the reluctance of those with undiagnosed symptoms to seek help or comply with treatment [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In rural and remote settings, nurses find that patients with mental health concerns, who often present with highly complex needs, are challenging to manage; there is little backup, fewer resources (such as detox centres), and no on-hand mental health specialist services (Beks et al 2018;Brunero et al 2018;Caxaj 2016;Kidd et al 2012;Wideman et al 2020). While caring for patients with mental health concerns in general acute care settings has been acknowledged (Beks et al 2018;Kidd et al 2012;Link et al 2019), less recognized is the inclusion of mental health nursing care within nurses' generalist practice in primary care and community settings (Wideman et al 2020) and within LPNs' practice in long-term care.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the literature that discusses this stigma only in the context of professional practice interactions (Brunero et al . 2018 ) or the workplace (Moore et al . 2010 ), the nurses in this study noted how mental health stigma affected their lives in rural and remote communities.…”
Section: Discussionmentioning
confidence: 99%